2020
DOI: 10.1002/bab.1956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenolic compounds from the leaves of Psidium guajava on the activity of three metabolism‐related enzymes

Abstract: Enzyme activity modulation by synthetic compounds provide strategies combining the inhibitory and therapeutic mode of action of the confirmed inhibitors. However, natural modulators could offer a valuable alternative for synthetic ones for the treatment of different chronic diseases (diabetes, hypertension, cancer); due to the numerous side effects of the latter. In vitro screening assays were conducted for Psidium guajava leaf methanolic extract against three metabolism-related enzymes; α-amylase, tyrosinase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…In addition to the six main biological activities mentioned above, EA also has biological activities such as anti‐pulmonary fibrosis (Vu et al, 2019), anti‐atherosclerosis (José‐Luis et al, 2018), anti‐diabetes (Stojanović et al, 2017), anti‐depression (Huang et al, 2020), improving liver cirrhosis (Reis et al, 2017), the improvement of the side effects caused by some drugs (Ahmed et al, 2020), and other biological activities.…”
Section: Bioactivity Of Ellagic Acidmentioning
confidence: 99%
“…In addition to the six main biological activities mentioned above, EA also has biological activities such as anti‐pulmonary fibrosis (Vu et al, 2019), anti‐atherosclerosis (José‐Luis et al, 2018), anti‐diabetes (Stojanović et al, 2017), anti‐depression (Huang et al, 2020), improving liver cirrhosis (Reis et al, 2017), the improvement of the side effects caused by some drugs (Ahmed et al, 2020), and other biological activities.…”
Section: Bioactivity Of Ellagic Acidmentioning
confidence: 99%
“…The cosmetic industry, in particular, could find new applications for these residues, especially taking into account the wide array of promising properties they have exhibited, such as antioxidant, depigmenting, seborregulator, exfoliant, and antiaging [21,124]. A relevant example due to its high market demand is the antiaging potential of the cork extracts: several compounds found in cork extracts have demonstrated the ability to inhibit enzymes such as collagenase, elastase [125,126], hyaluronase and tyrosinase [127,128], all of which play a key role in skin aging. However, it is not clear whether these compounds retain such biological activities when isolated from cork by-products, or if that ability results from synergistic effects.…”
Section: Discussionmentioning
confidence: 99%
“…This was thought to be due to an increase in the total phenolic content of tapioca noodles, especially the addition of guava leaves. Ahmed et al (2021) showed that guava leaf extract had a strong inhibitory effect on the α-amylase enzyme, mainly due to its anthraquinone and ellagic acid content. In vivo research supported the result that guava leaf extract could reduce blood sugar levels in diabetic rats through the inhibition of α-amylase and glucose transport enzymes (Shabbir et al, 2020).…”
Section: Degree Hydrolysis With α-Amylase Enzymementioning
confidence: 99%